2014
DOI: 10.1109/jqe.2014.2327015
|View full text |Cite
|
Sign up to set email alerts
|

Stable Scanning of Dressing Fields on Multiwave Mixing in Optical Ring Cavity

Abstract: We investigate a novel detection technique to study the coherent control of dressed multiwave mixing (MWM) process. A stable laser dressing field with a wavelength of 480 nm is realized via the second harmonic generation technique. By scanning such dressing field, stable Rydberg MWM signals with high signal-to-noise ratio are observed. With the MWM signals oscillated in a stabilized three-mirror cavity and cavity dressing field scanned, dressed MWM cavity modes are obtained. Thanks to the stable 480 nm and cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Stable locking behavior is a generic property in many coupled systems 22 26 , and lateral laser arrays are no exception 12 , 17 19 . Previous bifurcation analyses have shown that stable locking regions can be found in two- and three-element laser arrays and depend strongly on the degree of amplitude-phase coupling of the lasing field that is characterized by the linewidth enhancement factor 12 , 18 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Stable locking behavior is a generic property in many coupled systems 22 26 , and lateral laser arrays are no exception 12 , 17 19 . Previous bifurcation analyses have shown that stable locking regions can be found in two- and three-element laser arrays and depend strongly on the degree of amplitude-phase coupling of the lasing field that is characterized by the linewidth enhancement factor 12 , 18 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…A long stroke PZT is mounted on the back of M1 to adjust and control the cavity length. Also, the feedback electronic signal for holding the cavity length is also added onto the cavity through the PZT [18]. The 7cm long atomic vapor cell (placed between M2 and M3) is wrapped with μ-metal sheets and heated by a heater tape to set the temperature of the cell as 60°C to provide an atomic density of 2.5 × 10 11 cm −3 .…”
Section: Introductionmentioning
confidence: 99%